PERAN PENYULUH AGAMA KRISTEN DALAM MEMBANGUN KARAKTER RELIGIUS WARGA BINAAN MASYARAKAT RUTAN KELAS LLB KABUPATEN MAMUJU - Sinrayanti Ewanan; Albir Resua (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This study aims to describe and analyze the role of Christian religious instructors in shaping the religious character of inmates in Class IIB Penitentiary in Mamuju Regency. This study uses a qualitative approach with a library study method. Data were obtained from various relevant literature such as books, scientific journals, and religious documents that discuss the role of instructors, character building, and the dynamics of spiritual life in correctional institutions. The results of the study indicate that Christian religious instructors act as agents of spiritual transformation through pastoral care, spiritual guidance, and comprehensive faith building. Religious character is formed holistically, covering cognitive, affective, and real-life aspects of inmates. Obstacles in implementing counseling include limited facilities, bureaucracy, and the lack of number and competence of instructors. However, counseling has been shown to have a significant impact on the process of repentance, behavioral change, and readiness of inmates to return to society intact and with dignity. This study recommends strengthening the synergy between the government, church, and community to support sustainable religious counseling in correctional environments.